KARAKTER DISIPLIN SISWA KELAS V SEKOLAH DASAR DALAM PERSPEKTIF PERAN ORANG TUA - Fina; Etik; Rosmalah Yanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the discipline character of fifth-grade elementary school students from the perspective of parental roles. The study employed a descriptive qualitative approach using a case study design. The research was conducted at SDN 036 Rante Paccu, Baebunta Village, Baebunta District, North Luwu Regency, Indonesia. The research participants consisted of the fifth-grade classroom teacher and fifth-grade students. Data were collected through observation, interviews, and documentation, and were analyzed using the Miles and Huberman interactive analysis model, which includes data reduction, data display, and conclusion drawing. The findings indicate that the discipline character of the fifth-grade students has not yet developed optimally. This is reflected in the fact that some students still arrive late at school, fail to complete assignments on time, show a lack of discipline during the learning process, and do not fully comply with school regulations. From the perspective of parental roles, the development of students' discipline character is hindered by challenges related to habituation, role modeling, supervision, and communication. Parents' busy work schedules result in inconsistent guidance at home, while supervision of children's learning activities and gadget use remains limited. These findings suggest that fostering students' discipline character requires stronger collaboration between parents and schools so that disciplinary values can be consistently cultivated in both the family and school environments.